Composition of heterotrophic specialized sub-guilds defined by a positive RNA and polyhydroxyalkanoate correlation in activated sludge. (1st November 2018) - Guo, Bing; Manchester, Marie; Luby, Theresa; Frigon, Dominic
Abstract: Microbial heterotrophic guilds in activated sludge wastewater treatment systems have complex population structures and functions. A previously proposed heterotrophic-specialist model states that heterotrophs consist of sub-guilds specialized in consuming specific classes of compounds, either readily degradable substrate (RDS) or slowly degradable substrate (SDS) according to current mathematical modeling practices for wastewater treatment processes. It follows from metabolic considerations that the levels of RNA and polyhydroxyalkanoate (PHA) are correlated for strains of the same species growing in different environments; a conjecture previously tested. The proposed classification of heterotrophs into RDS or SDS consumers predicts that the same correlation would also be found across heterotrophic species in conventional activated sludge systems; this prediction was tested in the current study. The positive correlation between the RNA and PHA levels was observed in 9 conventional activated sludge plants in two independent sampling times and it was also found stable over a 6-month regular sampling period at one of these plants. Together, these results imply that the levels of RNA and PHA can be used to define heterotrophic-specialist sub-guilds. In order to gain insight in the species composition of the defined sub-guilds, flow cytometry cell sorting was used to further analyze one of the activated sludge samples. Four sorted sub-samples were obtained (high-RNA/high-PHA, low-RNA/high-PHA, high-RNA/low-PHA, and low-RNA/low-PHA), and the phylogenetic composition of each was determined using 16S rRNA gene amplicon pyrosequencing. Heterotrophic genera were identified across 12 phyla, and their representation in each sorted sub-sample showed that the high-RNA/high-PHA and low-RNA/low-PHA groups were most dissimilar. The enriched genera in these sorted sub-samples are suggested to represent the composition of heterotrophic-specialized sub-guilds defined by the kinetics of substrate consumption. Graphical abstract: Image 1 Highlights: Theory on specialization of heterotrophs predicted correlation between RNA and PHA. Flow cytometry revealed predicted positive RNA/PHA correlation in activated sludge. Positive RNA/PHA correlation observed at 9 activated sludge plants in two seasons. RNA/PHA correlation observed in 18 samples over 6 months at one treatment plants. Cell sorting identified taxa in high RNA/high PHA and low RNA/low PHA sub-guilds.